2012
DOI: 10.5897/ajmr12.1270
|View full text |Cite
|
Sign up to set email alerts
|

Incidences and antimicrobial susceptibility profile of Staphylococcus species isolated from animals in different Qatari farms

Abstract: This study was conducted during a six months period (March to August 2008) at the Veterinary laboratory, Department of Animal Resources, Doha, Qatar to determine the incidence of different bacterial genera farm animals in particular the occurrence of Staphylococcus species. The samples were from the rectum, milk, feces, nasal, swab of vagina, cloacal -uterin, intestine, liver and pus. Samples were collected from various animals of different regions. A total 318 of 429 samples gave positive results for Gram-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
(24 reference statements)
3
3
0
Order By: Relevance
“…This was also reported in other studies [42, 43]. Bhatt et al [44] reported isolation of high proportion of multidrug-resistant Staphylococcus organisms from surgical wounds.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This was also reported in other studies [42, 43]. Bhatt et al [44] reported isolation of high proportion of multidrug-resistant Staphylococcus organisms from surgical wounds.…”
Section: Discussionsupporting
confidence: 82%
“…The susceptibility of coagulase-negative Staphylococcus in this study was least in Ampicillin and Tetracycline; a study by Al-Thani and Al-Ali [42] reported Staphylococcus species to be resistant to Tetracycline, Penicillin, and Ampicillin in different Qatari farms. However, the same study reported the organisms being very susceptible to Cephalothin, Norfloxacin, and Co-trimoxazole.…”
Section: Discussionmentioning
confidence: 49%
“…The isolates showed high resistance (74.7% and 50.4%) to Tetracycline and Ampicillin respectively while 41.2% of the isolates were resistant to Methicillin and produced β-lactamase enzyme ( Figure 1). The observed variation in the percentage susceptibility profile expressed by S. aureus in this study also concurred with the report of Roda and Fatema [22] who observed a variation of 3 to 66.66%. The study of Roda and Fatema [22] and the work of Yaqub et al, [23,24] also observed high resistance to penicillin and tetracycline.…”
Section: Discussionsupporting
confidence: 92%
“…The observed variation in the percentage susceptibility profile expressed by S. aureus in this study also concurred with the report of Roda and Fatema [22] who observed a variation of 3 to 66.66%. The study of Roda and Fatema [22] and the work of Yaqub et al, [23,24] also observed high resistance to penicillin and tetracycline. This could be associated with the vast used of these antibiotics for the treatment of animal diseases [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation